2019
DOI: 10.1038/s41598-019-45016-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of radiotherapy after surgery in de novo stage IV breast cancer: a population-based propensity-score matched analysis

Abstract: The survival benefit from radiotherapy in stage IV breast cancer has not been fully evaluated. We investigated the survival benefit of radiotherapy after surgery in de novo stage IV breast cancer. Using a population-based database (the Surveillance, Epidemiology, and End Results database 18, 2010–2013), patients diagnosed with de novo stage IV breast cancer were divided into those undergoing surgery alone (no-radiotherapy group) and those undergoing surgery followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
(34 reference statements)
2
22
0
Order By: Relevance
“…Although the efficacy of local treatment in these patients showed contradictory results in prospective studies (8)(9)(10)(11), current retrospective studies with large cohorts had suggested that local treatment could improve the survival of this patient subset (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, most studies are mainly based on surgical treatment, and there are currently no prospective studies to compare the role of radiotherapy and surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the efficacy of local treatment in these patients showed contradictory results in prospective studies (8)(9)(10)(11), current retrospective studies with large cohorts had suggested that local treatment could improve the survival of this patient subset (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, most studies are mainly based on surgical treatment, and there are currently no prospective studies to compare the role of radiotherapy and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, four recent randomized trials that investigated prognosis after surgery in de novo stage IV breast cancer reported conflicting results (8)(9)(10)(11). Several retrospective studies have shown a survival advantage with locoregional treatment, including surgery or radiotherapy to the primary site (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The rationale for proceeding with additional surgery or radiotherapy includes the possibility of increasing the effectiveness of chemotherapy, reducing the total tumor burden, restoring immunity, eliminating breast cancer stem cells, and decreasing the likelihood of resistant disease, which may lower the metastatic potential of the primary tumor (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Current discussions as to whether adding radiotherapy to surgery can bring additional effects to surgery alone are an active topic of debate. Only one study has focused on this area: Yi-jun Kim et al evaluated the efficacy of adding radiotherapy to surgery in their study and concluded that combined treatment may increase the survival rate in dnMBC patients when compared with surgery alone ( 19 ). We feel that not considering the status of systemic treatment is a big limitation of their study.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, advances in molecular biology have contributed to significant improvements in the diagnosis and classification of breast cancer ( 2 , 3 ). Surgery, radiotherapy and chemotherapy (hormone and targeted) have shown remarkable survival benefits in patients with breast cancer ( 4 ). Approximately 30% of breast tumors overexpress human epidermal growth factor receptor 2 (HER-2) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%